Scaling Effect of Long Rod Penetration - Partom, Yehuda (European Journal of Applied Sciences, 2023)
Long rod penetration tests show a scaling effect that cannot be explained by rate dependent strength. We propose here that such a scaling effect may be explained by a rate dependent failure response. We start by revisiting the well-known result that long rod penetration efficiency depends on strain to failure of both projectile and target materials. We then make the strain to failure depend on strain rate, using our overstress approach concept. With this approach, the effective strain to failure increases with strain rate. As strain rate increases with decreasing scale, we also get that penetration efficiency decreases with decreasing scale, which has been observed in tests. In the paper we show results of hydrocode runs that demonstrate the relation between the strain rate sensitivity of strain to failure and the scaling effect of long rod penetration